TEACHER PROFESSIONALISM IMPROVEMENT MANAGEMENT: STUDY OF PRINCIPAL LEADERSHIP AT SMA AL-ITTIHAD KARANG TENGAH CIANJUR - Undang Ruslan Wahyudin; Dudung Winara; Hinggil Permana (JURNAL AL-TANZIM, 2021)
This research is motivated by the fact that at Al-Ittihad High School, there is a lack of awareness of students towards the practice of religion. This study aimed to determine the principal's program in planning, organizing, implementing, supervising, supporting, and inhibiting factors from improving the professionalism of teachers at Al-Ittihad High School. This research is qualitative descriptive field research. They are collecting data using interviews, observation, and documentation methods. Analysis of the data used is a qualitative analysis consisting of three components of analysis: data reduction, data presentation, and concluding. All three are carried out interactively with the data collecting process as one cycle. The results show that planning is done by improving the quality of teachers, continuing education to a higher level, providing adequate honorarium incentives, involving teachers in training, workshops, seminars, workshops, and so on.